Policy Orientation, Technological Innovation and Energy-Carbon Performance: An Empirical Study Based on China’s New Energy Demonstration Cities - Zhang, Xiaoyi; Zhang, Rui; Zhao, Meilin; Wang, Yue; Chen, Xue (Frontiers in Environmental Science, 2022)
The new energy demonstration city policy is a significant pilot measure to promote the transition of China’s energy system, aiming at developing new, green, and low-carbon sources of energy. In this paper, the Non-radial Directional Distance Function (NDDF) was adopted to calculate the Energy-Carbon Performance Index (ECPI) of Chinese 182 cities, for measuring the Energy-Carbon Performance (ECP) level of each city. On this basis, it is possible to empirically analyse the impact that the policy orientation of constructing new energy demonstration cities has had on urban energy carbon performance by using a combination of Propensity Score Matching and Difference-in-Difference. Moreover, a mediating effect model is utilised to test the mediating effect of technological innovation. The results show that the new energy demonstration city policy can significantly improve the ECP. Technological innovation has a partial mediating effect between the policy orientation of new energy demonstration city construction and ECP, which accounts for 12.92% of the total effect. Optimising the industrial structure, improving the level of economic development, increasing carbon sink resources, and attracting foreign direct investment all have significant impacts on the improvement of China’s ECP, while the urbanisation process has an inhibitory effect on the improvement of ECP. Heterogeneity analysis shows that policy orientation has a better driving effect on eastern cities and western cities in promoting the improvement of ECP. The policy implications of this paper are that 1) The government should expand the scope of new energy city pilots in an orderly manner; 2) The lasting and long-term influence of policy orientation on ECP should make use of technological innovation intermediary channels; 3) Support policies are supposed to formulate according to local conditions.